2018
DOI: 10.1007/s00442-018-4216-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of changes in water and nitrogen availability on alien plant invasion into a stand of a native grassland species

Abstract: Plant invasions are a major component of global change, but they may be affected by other global change components. Here we used a mesocosm-pot experiment to test whether high water availability, nitrogen (N) enrichment and their interaction promote performance of three invasive alien plants (Lepidium virginicum, Lolium perenne and Medicago sativa) when competing with a native Chinese grassland species (Agropyron cristatum). Single plants of the three invasive and the one native species were grown in the cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…However, the results of Spearman correlation analysis showed that the limiting factor for the real-time decomposition rate in our study was not N concentration but P concentration (p < 0.05, S3 Table ). Consistent with the decomposition rate, the real-time decomposition rate also had significantly negative correlation with C concentration and C/N ratio [19,52,72]. C/N ratio could reflect the ratio of carbohydrates to proteins which is an essential property of litter [73].…”
Section: Plos Onesupporting
confidence: 52%
“…However, the results of Spearman correlation analysis showed that the limiting factor for the real-time decomposition rate in our study was not N concentration but P concentration (p < 0.05, S3 Table ). Consistent with the decomposition rate, the real-time decomposition rate also had significantly negative correlation with C concentration and C/N ratio [19,52,72]. C/N ratio could reflect the ratio of carbohydrates to proteins which is an essential property of litter [73].…”
Section: Plos Onesupporting
confidence: 52%
“…In an environment where water and nutrients availability is high, the invasive species, Lepidium virginicum and Medicago sativa , produced more biomass. [ 50 ] In one case, addition of P with N favored the growth performance of Pterocypsela laciniata and had a relatively smaller effect on the growth of Solidago canadensis , because P. laciniata may have a higher P requirement than S. canadensis . [ 14 ] In our case, invasive A. philoxeroides benefited from P addition with N (P+N−) at 50% irrigation and showed good growth performance and better biomass production compared to 25% irrigation in both natural and nutrient soils.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid globalization, more and more plant species have been introduced to new regions outside their native range (van Kleunen et al 2015;Seebens et al 2018;van Kleunen et al 2018). Some of these alien plants have become invasive, which could decrease native species diversity, change nutrient cycles, and thereby affect ecosystem functions (Hejda et al 2009;Vilà et al 2011;Pyšek et al 2012;Linders et al 2019;Pyšek et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, soil fauna could enhance nutrient mineralization, and thereby increase plant nutrient uptake (Smith and Steenkamp 1992; Marinissen and de Ruiter 1993; Bardgett and Chan 1999; Xu et al 2003; Cole et al 2004; Barot et al 2007; Eisenhauer et al 2010). Given that invasive plants frequently respond more positively to nutrient enrichment than native plants (Liu et al 2017; Liu et al 2018), the higher nutrient availability caused by soil fauna may increase the invasion success. On the other hand, soil fauna can also change alien-native competition via herbivory effects (Bonkowski et al 2009; Korell et al 2019).…”
Section: Introductionmentioning
confidence: 99%